2016
DOI: 10.1017/s0950268816001795
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity and epidemiology of human parechovirus types 1, 3, and 6 in Japan

Abstract: Human parechoviruses (HPeVs) mainly infect young children, causing mild gastrointestinal and respiratory diseases; however, HPeV type 3 (HPeV3) causes severe systemic diseases in young infants. To clarify the characteristics of HPeV infections from the aspects of seropositivity and epidemiology, we measured neutralizing antibody titres against HPeVs in individuals of in different age groups and isolated HPeVs from various clinical specimens in Niigata, Japan. The seropositivity to HPeV1, 3, and 6 was higher in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
40
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(54 citation statements)
references
References 22 publications
10
40
0
4
Order By: Relevance
“…PeV-A1 detections occurred earlier than PeV-A3, agreeing with seroprevalence findings [10,11], but conflicting with RT-PCR-based studies [11,31]. However, the RT-PCR studies relied upon clinical samples, which may bias the PeV detection ages as PeV-A3 is associated primarily with disease before age 3 months [2,3,5,7,11]. Unlike stools, PeV was detected rarely in nasal swabs (0.2%) and was always associated with a PeV-positive stool of the same genotype, supporting fecal-oral as one transmission route.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…PeV-A1 detections occurred earlier than PeV-A3, agreeing with seroprevalence findings [10,11], but conflicting with RT-PCR-based studies [11,31]. However, the RT-PCR studies relied upon clinical samples, which may bias the PeV detection ages as PeV-A3 is associated primarily with disease before age 3 months [2,3,5,7,11]. Unlike stools, PeV was detected rarely in nasal swabs (0.2%) and was always associated with a PeV-positive stool of the same genotype, supporting fecal-oral as one transmission route.…”
Section: Discussionsupporting
confidence: 86%
“…PeV infection risk increased during summer, in agreement with some [2,3,7,11,15], but not all studies as late autumn peaks are also reported [6,11,13,15]. Presence of older household siblings was not associated with PeV or PeV-A3 infections within ORChID, a finding contrasting with hospital-based studies focusing mainly on PeV-A3 cases [33,34].…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Like enteroviruses, the epidemiology and clinical syndromes associated with HPeV vary by genotype 5 . HPeV1 and HPeV6 are primarily associated with milder gastrointestinal symptoms and presentation in children aged > 6 months 18 , 19 . HPeV may be isolated from respiratory specimens in children presenting with influenza‐like illness 20 and in faecal specimens from children presenting with viral diarrhoea 21 …”
Section: Clinical Presentation and Complicationsmentioning
confidence: 99%